Sunday
March 26, 2017

Post a New Question

Posted by on .

solve the following exponential equation

e^x-4=-e^-x

when I work i get

x-In(u)
is this correct

  • math - ,

    We left off at that point in my previous answer. Apparently you did not do much work thereafter.

    If you let u=e^x, your equation becomes

    u-4 = -1/u
    u^2 - 4u + 1 = 0
    u = 2±√3

    since u=e^x, x=ln(u)
    so, x = ln(2+√3) or ln(2-√3)

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question